Spatial Distribution of Macrozoobenthos in Relation toOceanographic Parameters in the Marine Waters Surrounding TundaIsland - Ramadhani, Novia; Silaban, Joy Elisabeth; Ramadhani, Tirta Samudera; Minsaris, Ode Alam; Dipura, Raflian Khansa; Silaban, Samuel; Fauzia, Syifa; Puspita, Lingga Diva; Anra, Nur'aini Dwi; Squire, Keelan (Jurnal Penelitian Geografi, 2025)
This study explores the spatial distribution of macrozoobenthos in relation to oceanographic parameters in the waters surrounding Pulau Tunda, Banten. A combination of remote sensing data namely sea surface temperature (SST), salinity, chlorophyll-a concentration, and bathymetry was utilized alongside direct field sampling at three designated stations. Oceanographic data were extracted from Landsat 8 imagery and GEBCO bathymetric sources, processed using ArcGIS Pro and Global Mapper. The Shannon-Wiener and Simpson indices were applied to assess biodiversity and species dominance. Results reveal that areas exhibiting SST between 28–31°C, moderate salinity levels (31–32 ppt), and high chlorophyll-a concentrations tend to support moderately diverse and stable benthic communities, predominantly composed of gastropods. The findings highlight the utility of remote sensing for habitat prediction and emphasize the ecological potential of Pulau Tunda's coastal waters.